Syndepositional precipitation of calcium sulfate in Gale Crater, Mars. (28th September 2018) - Kah, Linda C.; Stack, Kathryn M.; Eigenbrode, Jennifer L.; Yingst, R. Aileen; Edgett, Kenneth S.
Abstract: Lacustrine sedimentary rocks of the Murray formation, Gale Crater, Mars, contain evidence for early diagenetic mineral precipitation. High‐resolution MAHLI images permit detailed morphological and spatial analysis of these features. Millimetre‐scale lenticular features occur in massive to well‐laminated mudstone and are interpreted as pseudomorphs after gypsum. The distribution and orientation of lenticular features indicate deposition at or near the sediment–water or sediment–air interface, and the lenticular form suggests crystallization in the presence of organic constituents. Original crystals were likely poikilotopic (i.e., incorporating elements of the matrix), and the original mineralogy was lost during later diagenetic fluid flow. Evidence for lenticular gypsum imaged in Gale Crater, along with earlier observations of potential early diagenetic evaporite precipitation made by the Opportunity rover, indicate that deposition of evaporitic sulfate minerals may have been widespread on early Mars.